Elementary Steps of Faujasite Formation Followed by in Situ Spectroscopy - Prodinger, Sebastian; Vjunov, Aleksei; Hu, Jian Zhi; Fulton, John L; Camaioni, Donald M; Derewinski, Miroslaw A; Lercher, Johannes A (Chemistry of materials, 2018)
Ex situ and in situ spectroscopy was used to identify the kinetics of processes during the formation of the faujasite (FAU) zeolite lattice from a hydrous gel. Using solid-state 27Al magic angle spinning (MAS) nuclear magnetic resonance (NMR), the autocatalytic transformation from the amorphous gel into the crystalline material was monitored. Al X-ray absorption near-edge structure shows that most Al already adopts a tetrahedral coordination in the X-ray-amorphous aluminosilicate at the beginning of the induction period, which hardly changes throughout the rest of the synthesis. Using 23Na NMR spectroscopy, environments in the growing zeolite crystal were identified and used to define the processes in the stepwise formation of the zeolite lattice. The end of the induction period was accompanied by a narrowing of the 27Al and 23Na MAS NMR peak widths, indicating the increased level of long-range order. The experiments show conclusively that the formation of faujasite occurs via the continuous formation and subsequent condensation of intermediary sodalite-like units that constitute the key building block of the zeolite.